Strategies and Technologies for Preparing Mentally Disabled Children for Social Life - Abdumutal Olimovich Abdunazarov (Scientific Trends, 2024)
This article discusses the education and upbringing of mentally disabled children, focusing on their adaptation to society and social life. It highlights the wide range of opportunities and conditions created for the education of such children and elaborates on their preparation for independent activity. The peculiarities of adapting mentally disabled children to social life, along with the essence of this issue, are examined. The main goals and objectives of special boarding schools and the necessity of constant collaboration between stakeholders to develop independent life skills in mentally disabled children are substantiated.
Keywords: Mentally disabled, children with special needs, social, special education, clinical-pedagogical, oligophrenia, endogenous, exogenous, genetic factors, mental retardation, dementia, imbecility, idiocy.